Patient-derived lung cancer organoids as in vitro cancer models for therapeutic screening - Minsuh Kim (Nature Portfolio, 2019)
The clinical efficacy of standard therapy in lung cancer is limited by high level of heterogeneity. Here, the authors report patient-derived lung cancer organoids from different histological subtypes and show them to faithfully recapitulate the histology, genomics, and drug responses of the primary lung tumours.